2018
DOI: 10.1039/c8cy01601a
|View full text |Cite
|
Sign up to set email alerts
|

Dry reforming of methane over Co–Mo/Al2O3 catalyst under low microwave power irradiation

Abstract: In this work, microwave (MW) irradiation was used to activate Co/Al2O3, Mo/Al2O3, and Co–Mo/Al2O3 catalysts for dry reforming of methane (DRM) reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 65 publications
(72 reference statements)
5
25
0
Order By: Relevance
“…Recently, microwave catalytic reactions have attracted great attention because they greatly accelerate the reaction rate under mild conditions and significantly improve selectivity. In addition, certain chemical reactions that are not possible in CRM can be triumphantly carried out in MCRM . In addition, compared with conventional heating methods, microwave irradiation can reduce the energy consumption of the reaction. It is well known that microwave is an energy-efficient method and thus can be used to lower the energy consumption of the DRM reaction. , Stiegman et al reported that microwave irradiation can accelerate the oxidation of carbon dioxide to coke and accelerate the removal rate of coke . Our group recently studied microwave catalytic H 2 S and found that microwave irradiation can not only reduce the reaction temperature but also break the thermodynamic equilibrium limit to achieve highly efficient decomposition of hydrogen sulfide at low temperature. , Some researchers have used microwave irradiation for the DRM reaction. ,, Fidalgo et al reported microwave-assisted DRM over carbon-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, microwave catalytic reactions have attracted great attention because they greatly accelerate the reaction rate under mild conditions and significantly improve selectivity. In addition, certain chemical reactions that are not possible in CRM can be triumphantly carried out in MCRM . In addition, compared with conventional heating methods, microwave irradiation can reduce the energy consumption of the reaction. It is well known that microwave is an energy-efficient method and thus can be used to lower the energy consumption of the DRM reaction. , Stiegman et al reported that microwave irradiation can accelerate the oxidation of carbon dioxide to coke and accelerate the removal rate of coke . Our group recently studied microwave catalytic H 2 S and found that microwave irradiation can not only reduce the reaction temperature but also break the thermodynamic equilibrium limit to achieve highly efficient decomposition of hydrogen sulfide at low temperature. , Some researchers have used microwave irradiation for the DRM reaction. ,, Fidalgo et al reported microwave-assisted DRM over carbon-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the preparation process is a bit cumbersome and the calcination temperature is high up to 1000 °C. Liu et al developed a Co-Mo/Al 2 O 3 catalyst for DRM under microwave irradiation and found that compared with carbon-based catalysts, Co-Mo/Al 2 O 3 catalysts have better activity and stability . Although some researchers have applied microwave irradiation in DRM reactions, , most of these reaction systems use carbon-based catalysts, which are not very stable.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations